Investigation of the association between gall bladder wall thickness and hypoalbuminaemia in dogs. (12th July 2021) - Sparago, J.; Rademacher, N.; Dehghanpir, S.; Post, J.; Liu, C. C.; Johnston, A. N.
Abstract : Objectives: To assess the correlation between gallbladder wall thickness and serum/plasma albumin concentrations in dogs. Materials and Methods: Retrospective searches of digital medical record databases were conducted to identify dogs that had either severely low serum/plasma albumin concentration (<1.5 g/dL) or ultrasonographic evidence of gallbladder wall thickening (>2 mm). Analysis of covariance models were used to analyze gallbladder wall thickness with sample type (serum vs plasma), age, etiology, albumin, and albumin ' etiology as the covariates. Results: A total of 216 dogs met inclusion criteria. One‐hundred and forty‐six dogs had a thickened gallbladder wall (Group 1). Median serum/plasma albumin concentration for dogs in this group was 2.2 g/dL (1 to 5 g/dL), and 84 dogs (57.5%) had hypoalbuminemia (<2.5 g/dL). The search for dogs with severe hypoalbuminemia (< 1.5 g/dL) identified 70 dogs (Group 2). In this group, median gallbladder wall thickness was 1.3 mm (0.2 to 6.1 mm) and 17 dogs (24.3%) had a thickened gallbladder wall. Serum/plasma albumin concentration and gallbladder wall thickness were not significantly correlated for Group 1 (r = 0.0044, p = 0.9580) or Group 2 (r = ‐0.1137, p = 0.3487). A moderate negative correlation (‐0.64) was identified between gallbladder wall thickness and albumin concentration in dogs with immune‐mediated diseases (p = 0.03). Clinical Significance: Gallbladder wall thickness and serum/plasma albumin concentration are independent variables in dogs.